2019
DOI: 10.3390/w11051088
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Land Use Impacts on Channel Geomorphology and Streambed Sedimentological Characteristics

Abstract: Land use can radically degrade stream physical habitat via alterations to channel geomorphology and sedimentological characteristics. However, independent and combined influences such as those of agricultural and urban land use practices on channel geomorphology and substrate composition remain poorly understood. To further understanding of mixed land use influence on stream physical habitat, an intensive, 56 km hydrogeomorphological assessment was undertaken in a representative mixed land use watershed locate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Results further demonstrate the immense, globally transferrable value of the experimental watershed approach for municipal watersheds. Mixed land use influences on stream physical habitat was investigated by Zeiger and Hubbart [10] who directly measured channel geomorphology, and stream substrate composition every 100 m over 56 km (n = 561). Results showed that agricultural and urban land use explained nearly all the variance in average river width to depth ratios (R 2 = 0.960; p = 0.020; n = 5), and maximum bank angle (R 2 = 0.896; p = 0.052; n = 5).…”
Section: Experimental Study Designs and Modelingmentioning
confidence: 99%
“…Results further demonstrate the immense, globally transferrable value of the experimental watershed approach for municipal watersheds. Mixed land use influences on stream physical habitat was investigated by Zeiger and Hubbart [10] who directly measured channel geomorphology, and stream substrate composition every 100 m over 56 km (n = 561). Results showed that agricultural and urban land use explained nearly all the variance in average river width to depth ratios (R 2 = 0.960; p = 0.020; n = 5), and maximum bank angle (R 2 = 0.896; p = 0.052; n = 5).…”
Section: Experimental Study Designs and Modelingmentioning
confidence: 99%
“…Such results suggest water quality and aquatic habitat degradation in Hinkson Creek is not limited to the activities and spatial extent of the city of Columbia, but rather is a complex watershed-scale issue involving integrated anthropogenic and natural processes. Similarly, a physical habitat assessment (PHA) showed that Hinkson Creek is altered by agricultural and urban land uses [104,105] that have also impacted macroinvertebrate assemblages in Hinkson Creek. This information was important in CAM discussions, considering macroinvertebrates are key species indicating general aquatic ecosystem status [55,106].…”
Section: Experimental Watershed Design Outcomesmentioning
confidence: 99%
“…This information was important in CAM discussions, considering macroinvertebrates are key species indicating general aquatic ecosystem status [55,106]. Results from the PHA clearly identified agricultural and urban land use alterations to channel geomorphology [105]. Results also showed increased substrate embeddedness (e.g., 80% vertical embeddedness of pool habitats) in the agricultural headwaters and in the lower urbanized reaches of Hinkson Creek [105].…”
Section: Experimental Watershed Design Outcomesmentioning
confidence: 99%
“…As hydrology changes with land use, the amount of nutrients, sediment, or other anthropogenic contaminants entering waterways is also altered. Agricultural land has been linked to increases in nutrients and sediment in adjacent streams (Munn and others, 2018;Schmidt and others, 2019;Zeiger and Hubbart, 2019). To alleviate the effects of agricultural land use on freshwater systems, some agricultural producers have implemented conservation cropping practices such as no-till farming, use of cover crops when cash crops are not on the field, maintenance of riparian buffer zones, and precision application of nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…Besides being beneficial to farmers, keeping nutrients and sediment out of waterways helps aquatic ecosystems, because excess nutrients can lead to eutrophication and excess sedimentation from eroding soils can cause loss of habitat and harm to some aquatic species. Sedimentation can result in the loss of heterogeneity in streams due to fine sediment filling in pools and embedding gravel and cobble substrate (Munn and others, 2018;Zeiger and Hubbart, 2019).…”
Section: Introductionmentioning
confidence: 99%